Constraints to employment growth within the South African Automotive Industry - Burger, Elsje Emerentia (My University, 2013)
The research study set out to understand the factors constraining employment growth in the South African Automotive industry. This was particularly relevant in the context of the South African government’s renewed focus on growing employment, which has been shown to be the single best way to reduce poverty and increase economic participation by all classes in the South African economy (Briscoe 2000). As a key manufacturing sector, the South African Automotive Industry has the potential to drive employment growth, create sustainable, decent employment opportunities and aid in critical skills transfer and development. Identifying and classifying the impact of constraints on the industry would provide valuable guidance to government institutions mandated with growing employment by supporting this key sector. The information derived from the study would enable these institutions to prioritise projects and allocate limited resources and funding to the greatest effect. The research design was based on collecting in-depth, qualitative data through semi- structured interviews with selected key decision makers and experts in the industry. This allowed the researcher the ability to identify any additional constraints not highlighted in the original literature review, as well as to explore perceptions and reasoning behind responses provided during the interview. The study found the impact of key identified factors to be perceived differently for OEMs and component manufacturers, and the classification of constraints therefore had to distinguish between these sectors. For OEMs, raw material, as well as the cost of infrastructure was identified as significant constraints, while funding, labour skills and regulation were perceived as low constraints due to the OEM’s ability to leverage assistance from government and its global production network to mitigate these factors. Government policies and regulation was highlighted as a supporting factor in creating and sustaining employment. While raw material and infrastructure cost were also highlighted as significant constraints for the component manufacturing industry, the industry highlighted other factors, including export capability and labour skills as additional high impact ii constraints to the component industry. Contrary to OEMs, manufacturers viewed government policy as a constraining factor to employment, especially following changes made to policies under the MIDP and APDP. It is clear from the study that the majority of these bottlenecks often constitute structural constraints that could be addressed through relevant support and policies. This leaves substantial scope for translating correctly aligned policies and support into actual employment stability and growth. Identifying and prioritising these constraints will enable better coordination among government institutions and better application of limited funding and resources to achieve the greatest impact on the South African economy.
MBA thesis
Keywords: Employment; Labour relations; Human resources